2005
DOI: 10.1002/ejic.200500215
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Structures of Luminescent [2‐(Aminomethyl)pyridine]silver(I) Complexes: Effect of Ligand Ratio, Anion, Hydrogen Bonding, and π‐Stacking

Abstract: The reaction of 2‐(aminomethyl)pyridine (2‐amp) with silver(I) salts of triflate (OTf–), trifluoroacetate (tfa–), and tetrafluoroborate (BF4–) produce monomeric, dimeric, bridged, and polymeric structural motifs. The structural characteristics are dependent upon the ratio of ligand/metal in the structure as well as the ability of the anion to coordinate to the metal centers and form hydrogen bonds to the bound ligands. The silver coordination environment takes on several geometries including near linear (6), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 44 publications
3
38
1
1
Order By: Relevance
“…In our BPMP coordination studies with the tfa -ion, it was observed that the coordination of tfa -influences the formation of a structure unique from the structures isolated with the BF 4 -and 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 13 OTf -ions; this is also observed here [24,25]. Even though 2-pyridyl ligands are typically not capable of polymer formation due to the limited flexibility of the N pyridyl moiety, polymer structures are isolable when a counterion or solvent molecule coordinates to the metal center(s) preventing chelation [2,27,41]. The unique portion of the polymer features two distinct Ag(I) centers: a four-coordinate Ag1 and three-coordinate Ag2.…”
Section: Structure Of Compoundmentioning
confidence: 62%
See 2 more Smart Citations
“…In our BPMP coordination studies with the tfa -ion, it was observed that the coordination of tfa -influences the formation of a structure unique from the structures isolated with the BF 4 -and 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 13 OTf -ions; this is also observed here [24,25]. Even though 2-pyridyl ligands are typically not capable of polymer formation due to the limited flexibility of the N pyridyl moiety, polymer structures are isolable when a counterion or solvent molecule coordinates to the metal center(s) preventing chelation [2,27,41]. The unique portion of the polymer features two distinct Ag(I) centers: a four-coordinate Ag1 and three-coordinate Ag2.…”
Section: Structure Of Compoundmentioning
confidence: 62%
“…While the sterically less hindered DPAP-2 is important to formation of the large ring, the tfa -ion aids in the formation of the polymer. Although it is not uncommon to isolate structures with coordinating tfa -ions, the formation of the 1-dimensional polymer 3 is attributed to the bridging tfa -ions [24,25,[41][42][43][44][45][46][47].…”
Section: Structure Of Compoundmentioning
confidence: 98%
See 1 more Smart Citation
“…The possible reason is that the energy received by ligand is partially lost. It is noteworthy that this low energy luminescence is unusual, in comparison with the large numbers of blue emission Ag(I) coordination polymers [38,39] and representing a singular example with orange fluorescent property for potential uses as photoluminescence materials.…”
Section: Luminescent Propertymentioning
confidence: 99%
“…In the case of Ag(I), much work has been devoted to coordination of phosphine-and sulfur-based ligands [65], which are complementary to such a soft metal centre, while relatively little work has been directed toward luminescent assemblies based on N-heterocyclic ligands and Ag(I) [66]. Tetranuclear grid-like structures can be assembled with bis-bidentate Schiff-base ligands, which are readily obtained by condensation of diamines with 2-formyl pyridine (Fig.…”
Section: Assembly By Tetrahedral Metal Ionsmentioning
confidence: 99%